If f(x) = x^{2} then find \(\frac{f(2+h) – f(2)}{h}\)

Solution

Given

f(x) = x^{2}

We have to find \(\frac{f(2+h) – f(2)}{h}\) so,

f(2+h) = (2+h)^{2} = 4 + 4h + h^{2}

f(2) = 4

Now,

\( = \frac{f(2+h) – f(2)}{h}\)

\(= \frac{4 + 4h + h^2 – 4}{h} \)

\(= \frac{h(4 + h)}{h} \)

= 4 + h

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.

Click here to submit your answer.

Subscribe

Login

Please login to comment

0 Comments

HAMROCSIT.COM